Effects of Loading and Sliding Speed on the Dry Sliding Wear Behavior of Mg-3Al-0.4Si Magnesium Alloy. Issue 2 (4th March 2017) - Niu, X. D.; An, D. Q.; Han, X.; Sun, W.; Su, T. F.; An, J.; Li, R. G.
ABSTRACT: The friction and wear properties of Mg-3Al-0.4Si alloy were investigated using a pin-on-disc tester. Morphologies and compositions of worn surfaces were characterized by scanning electron microscopy (SEM) and energy dispersive X-ray spectrometry (EDS) for identification of the wear mechanisms. Microstructural evolution and hardness change in subsurfaces were analyzed by confocal scanning laser microscopy and hardness testing. The results revealed that the wear behavior of Mg-3Al-0.4Si alloy was classified into two types of wear regimes; that is, mild and severe. In the mild wear regime, wear rates increased at a low slope with increasing load; the corresponding wear mechanisms were oxidation, abrasion, and delamination. In the severe wear regime, wear rates increased rapidly at a high slope with load; the wear mechanisms were severe plastic deformation and surface melting. Analysis of microstructural evolution on the subsurface identified the reason for the transition from mild to severe wear; that is, the realization of dynamic recrystallization (DRX) in the surface layer material. A contact surface DRX temperature criterion for the mild to severe wear transition was proposed, and the critical DRX temperatures for the mild to severe wear transition were calculated using DRX kinetics.